Diversity of Saint Helena Island and zoogeography of zoantharians in the Atlantic Ocean: Jigsaw falling into place. Issue 2 (17th February 2019) - Santos, Maria E. A.; Wirtz, Peter; Montenegro, Javier; Kise, Hiroki; López, Cataixa; Brown, Judith; Reimer, James Davis
Abstract : Diversity surveys in isolated sites, such as oceanic islands, provide biogeographic data that can improve our analyses and knowledge of evolutionary processes in the oceans. Zoantharians (Cnidaria: Anthozoa) are common and widespread components of shallow-water reefs, but distributional analyses are scarce for this group. In this study, we collected Zoantharia specimens from around Saint Helena Island (STH) in the mid-Atlantic and identified species using external morphology and molecular data. Moreover, we compiled and analysed the most comprehensive distributional data for zoantharian species in the subtropical and tropical Atlantic Ocean to date. Our results show eight zoantharian species in STH, which includes seven new records for STH waters. Furthermore, all families and genera of the suborder Brachycnemina recorded are widespread in the Atlantic Ocean, including at least four amphi-Atlantic species. The Caribbean is the richness centre in the Atlantic Ocean for zoantharian species, a pattern similar to that observed for many other subtropical/tropical marine taxa. However, Zoantharia may have a lower endemism rate in some areas than other common reef animals, for example zooxanthellate scleractinian corals and reef fishes. Moreover, zoantharian species have a more extensive distribution than close-related taxa such as zooxanthellate scleractinian corals and hydrocorals in the Atlantic Ocean.